Whale! - Evans, Kim Leilani (University of Minnesota Press, 2003)
The aim of this thoroughly unconventional work is to demonstrate that Herman Melvilles Moby Dick and Ludwig Wittgensteins Philosophical Investigations are, in effect, one and the same book. Whale! not only successfully reveals the vital intersections between Melville and Wittgenstein but also makes a compelling argument for why such intersections are essential to understanding common political projects in literature and philosophy.